Perceptions of mental health care users on the contribution of the interactive groupwork model in occupational therapy groups to their recovery - Davidson, Shanay (Division of Occupational Therapy, 2019)
Background Mental health disorders account for a significant portion of the burden of disease in South Africa and places a substantial strain on the national mental health care system. Mental health care policy and service trends advocate for client-centred practices, whereby the needs and perspectives of the population being served are taken into account in the design and delivery of interventions. Mental health disorders affect people’s performance of and participation in the occupations of daily life. The profession of occupational therapy (OT) values clientcentred practice and seeks to offer interventions that are closely aligned with the occupational and related recovery concerns of mental health care users (MHCUs). The Interactive Groupwork Model (IGM) is an unpublished, South African OT model that is used to guide groupwork interventions in mental health care settings. It serves as the basis for a position statement on the role and scope of the profession in groupwork issued by the Occupational Therapy Association of South Africa (OTASA, 2014). Research Problem To date there is little literature documenting service users’ perspectives on groupwork in occupational therapy within the South African context. In particular, there is no published South African research in occupational therapy regarding mental health service users’ (MHCU) perspectives on the contribution of groups run according to the IGM to their recovery. Research Purpose This study contributes to the refinement of the Interactive Groupwork Model as one of a number of approaches to groupwork used by occupational therapists in South Africa. The information gained from the research will assist in creating relevant group based programmes for mental health care users who get admitted to mental health services where occupational therapy groups based on the IGM are offered. Research Question How do mental health care users perceive the contribution of the IGM to their recovery? Research Aim To describe the perspectives of users of mental health services about the contribution of IGM used in occupational therapy, to their recovery within a specialised psychiatric unit. Research Objectives Describe the perspectives of MHCU’s on the benefits of IGM for their recovery Describe the perspectives of MHCU’s on the limitations of IGM for their recovery Describe the recommendations of MHCU’s on the refinement of the IGM iv Research Design & Methodology A descriptive qualitative design positioned in a social constructivist paradigm guided the study methodology. Purposive maximum variation sampling was used. Data was collected using semi structured interviews with seven mental health care users during an eight or twelve-week admission period, at different stages of their recovery and community re-entry. Data was audio recorded and transcribed. Thematic analysis enabled the opinions of informants to be subcategorised and categorised. Ethical principles of beneficence, non-maleficence, autonomy and justice were upheld throughout the research process. Findings Participants’ perspectives on the contribution of occupational therapy groups using the IGM to their recovery was reflected in a single theme: “helping me to navigate life while living with my illness”. The theme was supported by two categories: “learning though the group space” and “learning that the journey is never over”. The learning that occurred in each category was supported by five sub-categories, each reflecting a dimension of how IGM based occupational therapy groups helped participants towards recovery: “engaging in the activity”, “participating in the group process”, “experiencing the group structure”, “recognising personal shifts” and “acknowledging stuckness”. Conclusion The research provided practice based evidence of service user perspectives on occupational therapy groupwork using the IGM. The IGM is beneficial as a change modality as it assists MHCUs with self-learning and addresses the interpersonal aspect of recovery during the acute intervention phase. With refinements considering the occupational human, and embracing the recovery philosophy, the IGM may offer greater value to MHCUs by addressing broader occupational engagement concerns that extend post discharge. The relevance of the IGM to the post discharge recovery of MHCU warrants attention if occupational therapy is to play a role in supporting MHCUs to live meaningful and productive lives through occupation. Recovery from serious mental illness is a complex lifelong process that is facilitated when health care professionals collaborate with MHCUs. Revisions to the OTASA position statement are suggested in an attempt to ensure that the OTASA position statement on groupwork represents a broader understanding of groupwork in the profession and specifically in mental health.